Biomass Sucrose‐Derived Cobalt@Nitrogen‐Doped Carbon for Catalytic Transfer Hydrogenation of Nitroarenes with Formic Acid. Issue 23 (26th October 2018) - Yuan, Man; Long, Yu; Yang, Jin; Hu, Xiwei; Xu, Dan; Zhu, Yangyang; Dong, Zhengping
Abstract: Fabrication of non‐noble metal‐based heterogeneous catalysts by a facile and cost‐effective strategy for ecofriendly catalytic transfer hydrogenation (CTH) is of great significance for organic transformations. A cobalt@nitrogen‐doped carbon (Co@NC) catalyst was prepared from renewable biomass‐derived sucrose, harmless melamine, and earth‐abundant Co(AcO)2 as the precursor materials by hydrothermal treatment and carbonization. Co nanoparticles (NPs) were coated with NC shells and uniformly embedded in the NC framework. The as‐obtained Co@NC‐600 (carbonized at 600 °C) catalyst exhibited excellent catalytic efficiency for CTH of various functionalized nitroarenes with formic acid (FA) as hydrogen donor in aqueous solution. The uniformly incorporated N atoms in the C matrix and the encapsulated Co NPs showed synergistic effects in the CTH reactions. A mechanistic analysis indicated that the protons from FA were activated by Co sites after being captured by N atoms, and then reacted with nitroarenes adsorbed on the surface of the catalysts to generate the corresponding aromatic amines. Moreover, the catalyst showed excellent durability and reusability without obvious decrease in activity even after five reaction cycles. Thus, the study reported herein provides a cost‐effective, sustainable strategy for fabrication of biomass‐derived non‐noble metal‐based catalysts for green and efficient catalytic transformations. Abstract : Give it some sugar : A cobalt nanoparticles@nitrogen‐doped carbon (Co@NC) catalyst is prepared from biomass‐derived sucrose, ecofriendly melamine, and earth‐abundant Co(AcO)2 . The Co@NC catalyst exhibits excellent catalytic efficiency for catalytic transfer hydrogenation (CTH) of various functionalized nitroarenes with formic acid as hydrogen donor in aqueous solution